Exploitable biomass status and potential of the Southeastern Anatolia Region, Turkey. Issue 1 (2nd January 2018) - Yılmaz, İbrahim Halil and Saka, Kenan
ABSTRACT: In this study, the exploitable biomass potential of nine provinces located in the Southeastern Anatolia region of Turkey was investigated. Animal- and vegetal-derived biomasses were taken into consideration in the analyses. The animal-derived biomass was handled as poultry, small ruminants, and cattle. The vegetal-derived biomass was accounted as field, garden, and vegetable crops. The contribution of each species on the biomass energy potential was studied. The available animal and vegetal residues in the region were estimated to be, respectively, equal to 6.2% and 9.4% of the corresponding residual amount in Turkey. The annual total biomass potential of the region was found to be approximately 83.4 PJ which could meet 15.7% energy demand of the region.